In-situ monitoring of woven glass fiber reinforced composites under flexural loading through embedded aligned carbon nanotube sheets. (August 2018) - Aly, Karim; Li, Ang; Bradford, Philip D
In practical situations, the flexural loading of fiber reinforced composites is one of the most common types of loading for structures. Nonetheless, carbon nanotubes, which have been used extensively to study in-plane strain sensing in composites, have rarely been employed to monitor flexural induced strains. With this motivation, this paper introduces a novel method for localizing aligned carbon nanotube sheet layers in three selected locations inside a laminated composite structure. These top, middle, and bottom locations are more prone to damage since they experience maximum flexural induced tension, compression, and interlaminar shear stresses. The composite structural performance is monitored by establishing an electromechanical coupling between the developing strain and the three carbon nanotube sensing elements' in-plane electrical resistance changes that are measured simultaneously. The results of the monotonic and dynamic flexural loading tests suggest that carbon nanotube sensing materials exhibit a high level of sensitivity. The results also show that the resistance change of the three embedded carbon nanotube layers appeared to track the mechanical state of the host structure well. The carbon nanotube layer embedded in the middle section showed a piezoresistive behavior in response to the growing complex stress state with a few electrical resistance change spikes corresponding to damage developing inside the laminated structure. This flexural sensing behavior may considered as useful for real applications because in addition to sensing strain, this technology may help in predicting the failure of the composite component before the actual end of service life.